Remote Nursing Assessment for Peritoneal Dialysis Users During Covid-19 Pandemic: An Systematic Review - Syaifoel Hardy; Ridha Afzal; Isak Jurun Hans Tukayo (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2021)
Abstract Chronic Kidney Disease nursing has become one of the centers of attention because of professional concerns about all the possibilities that occur in the handling of Peritoneal Dialysis (PD) users in health care centers in the era of Covid-19 pandemic. To maximize the achievement of the quality goals of nursing services, an updated nursing assessment system of PD users is needed during the pandemic. To identify changes in nursing assessment that occurred during the Covid-19 pandemic for PD users and offer a solution by creating a remote nursing assessment system. The study used an article review and PRISMA analysis. The initial 842 documents were drawn from the search engine of which 169 records extracted from Google Scholar, ResearchGate, SagePub, and Semantic Scholar. The search keywords were nursing assessment, PD users, and Covid-19. The indicators include respondents (PD users), research methods (quantitative, document review), years of publication (2020-2021), results (focus on nursing assessment during the Covid-19 pandemic), and languages (English and Indonesia). The document search used the PICOT (Population, Intervention, Comparison, Outcome, and Time). The PRISMA analysis finds remote nursing assessment during pandemic in handling PD users can be done in various health care services that have CAPD units. Yet it requires training and orientation programs. The challenges are the need for funds, time, and the readiness of human resources in which they were not mentioned in the previous researchers’ findings. Tele-PD-nursing, home delivery service, PD nursing triage, and a PD nursing dashboard are the combination of remote PD nursing management as an alternative solutions in PD users assessment during the Covid-19 pandemic era. Keywords: Remote Nursing Assessment, PD Users, Covid-19 Abstrak Keperawatan Penyakit Ginjal Kronik menjadi salah satu pusat perhatian karena kepedulian profesional terhadap segala kemungkinan yang terjadi dalam penanganan pengguna Peritoneal Dialysis (PD) di Puskesmas di era pandemi Covid-19. Untuk memaksimalkan pencapaian sasaran mutu pelayanan keperawatan, diperlukan sistem pengkajian keperawatan pengguna PD yang terupdate di masa pandemi. Untuk mengidentifikasi perubahan asesmen keperawatan yang terjadi selama pandemi Covid-19 bagi pengguna PD dan menawarkan solusi dengan membuat sistem asesmen keperawatan jarak jauh. Penelitian ini menggunakan tinjauan artikel dengan analisis PRISMA. 842 dokumen awal diambil dari mesin pencari yang 169 catatannya diambil dari Google Scholar, ResearchGate, SagePub, dan Semantic Scholar. Kata kunci pencarian adalah penilaian keperawatan, pengguna PD, dan Covid-19. Kriteria inklusi adalah pengguna PD selama pandemi, sedangkan kriteria eksklusi adalah pasien CKD tetapi bukan pengguna PD dan pengguna PD sebelum pandemi), metode penelitian (kuantitatif, tinjauan dokumen), tahun publikasi (2020-2021), hasil (fokus pengkajian keperawatan selama pandemi Covid-19), dan bahasa (Inggris). Pencarian dokumen menggunakan PICOT (Population, Intervention, Comparison, Outcome, dan Time). Analisis PRISMA menemukan bahwa pengkajian keperawatan selama masa pandemic dalam penanganan pasien pengguna PD dapat dilakukan di berbagai pusat pelayanan kesehatan yang memiliki unit CAPD. Namun dibutuhkan program pelatihan dan orientasi. Tantangannya berupa dana, waktu serta kesiapan SDM yang tidak disebutkan pada penelitian-penelitian terdahulu. Tele-PD-nursing, home delivery service, PD Nursing Triage, dan PD Nursing Dashboard merupakan kombinasi manajemen keperawatan PD jarak jauh sebagai solusi alternatif penilaian pengguna PD di masa pandemi Covid-19. Kata Kunci: Asesmen Keperawatan Jarak Jauh, PD User, Covid-19